Estudo da atividade antinociceptiva do peptídeo sintético PnPP-19 - Ana Cristina Nogueira Freitas (2018)
The toxin PnTx2-6, isolated from the venom of the spider Phoneutria nigriventer, is very toxic (LD50 = 0.7 μg/mouse) and has been studied as a molecule that improves erectile function. Besides this effect, this toxin induces local and systemic hyperalgesia in low doses (3 μg/animal). The synthetic peptide PnPP-19 represents a discontinuous epitope of the primary structure of the spider toxin PnTx2-6. PnPP-19 improves erectile function of rats and mice. This effect is similar of what is observed for the native toxin PnTx2-6. The present study investigated the role of PnPP-19 in the nociceptive pathway, since the toxin, of which the peptide originates from, induces hyperalgesia. Our data demonstrate that PnPP-19 induces a dose and timedependent central and peripheral antinociception. This antinociception is mediated by activation of CB1 cannabinoid receptors and μ- and δ-opioid receptors. The antihyperalgesic effect of the peptide may also involve the release of endocannabinoids, since the administration of non-analgesic doses of inhibitors of endocannabinoid reuptake and anandamide degradation have potentialized the antinociceptive effect of a low dose of the peptide. Increased levels of endogenous opioids might also be correlated with the antinociceptive effect of PnPP-19. This peptide may act as an inhibitor of the enzyme neprilysin, which is responsible for hydrolyzing several peptides in the extracellular site, among them, the endogenous opioid enkephalin. In addition, PnPP-19 administration may activate the neuronal and endothelial isoform of nitric oxide synthase, which causes an increase of nitric oxide levels. Furthermore, the antinociception triggered by PnPP-19 seems to be depending on cGMP levels and on the activation of ATP sensitive potassium channels. PnPP-19 may also act as a μ-opioid receptor agonist and it might modulate the influx of calcium in DRG neurons by the activation of these receptors. Activation of μ-opioid receptors induced by PnPP-19 does not appear to stimulate β- arrestin recruitment. Our results have shown the role of the synthetic peptide PnPP-19 in the nociceptive pathway, demonstrating at least part of the mechanism of action by which the peptide induces antinociception. Taking into account all our data, we suggest that PnPP-19 might be a useful tool for the development of new drug cadidates for pain treatment.